71.0k views
3 votes
4a² + 4ab-3b² = (2a+3b)(_)

Complete the factoring

User Baksteen
by
4.9k points

1 Answer

7 votes

Answer:

(2a + 3b)(2a - b)

Explanation:

4a² + 4ab - 3b²

consider the factors of the product of the coefficient of a² and b² which sum to give the coefficient of the ab- term.

product = 4 × - 3 = - 12 and sum = 4

the factors are + 6 and - 2

use these factors to split the ab- term

= 4a² + 6ab - 2ab - 3b² ( factor the first/second and third/fourth terms )

= 2a(2a + 3b) - b(2a + 3b) ← factor out (2a + 3b) from each term

= (2a + 3b)(2a - b)

User Sreyas
by
6.4k points